1965
DOI: 10.1149/1.2423574
|View full text |Cite
|
Sign up to set email alerts
|

The Catalysis of the Electrochemical Oxidation of Formaldehyde and Methanol by Molybdates

Abstract: The electrooxidation of formaldehyde and methanol on platinum has been shown to be catalyzed in sulfuric acid solution by the presence of molybdates. Decreased polarization has been shown to result from a cycle involving chemical reaction of the fuels with an oxidized molybdate species with subsequent electrooxidation of the reduced molybdate. The process requires the adsorption of molybdate at the electrode surface throughout the entire cycle.The existence of catalytic currents during the electrochemical reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 3 publications
0
30
0
2
Order By: Relevance
“…Second, Mo 2 C has a higher affinity for the methanol reactant than Pt/C (as revealed by STXM results) and has been demonstrated via EXAFS fitting analysis to interact strongly with the Pt nanoparticles. Third, in the presence of platinum, Mo 2 C nanotubes may have an active role in the electrochemical MOR, as reported by Shropshire 48 and Kita et al 11 The formation of hydroxyl groups from water activation is essential for the removal of CO poisoning from the surface; this role, played by ruthenium in the conventional PtRu/C catalysts, can also be filled by Mo 2 C. The MoO x layer on the surface of Mo 2 C nanotubes favours the adsorption of OH in solution and acts as a nanostructured OH reservoir for the MOR. Thus, the Mo 2 C nanotube-based catalysts A highly active, catalyst for methanol electro-oxidation K Zhang et al exhibit enhanced CO tolerance.…”
Section: Electrochemical Performancementioning
confidence: 68%
“…Second, Mo 2 C has a higher affinity for the methanol reactant than Pt/C (as revealed by STXM results) and has been demonstrated via EXAFS fitting analysis to interact strongly with the Pt nanoparticles. Third, in the presence of platinum, Mo 2 C nanotubes may have an active role in the electrochemical MOR, as reported by Shropshire 48 and Kita et al 11 The formation of hydroxyl groups from water activation is essential for the removal of CO poisoning from the surface; this role, played by ruthenium in the conventional PtRu/C catalysts, can also be filled by Mo 2 C. The MoO x layer on the surface of Mo 2 C nanotubes favours the adsorption of OH in solution and acts as a nanostructured OH reservoir for the MOR. Thus, the Mo 2 C nanotube-based catalysts A highly active, catalyst for methanol electro-oxidation K Zhang et al exhibit enhanced CO tolerance.…”
Section: Electrochemical Performancementioning
confidence: 68%
“…A long time ago, it was reported that adsorption of molybdates (Na 2 MoO 4 ) at a Pt black electrode before adding the fuel (HCHO or CH 3 OH) resulted in a decrease of 0.3 V in the oxidation onset potential with respect to pure Pt [Shropshire, 1965]. Moreover, when added to Pt-Ru catalysts, molybdenum led to higher activity with regard to methanol electro-oxidation at low potentials [Lima et al, 2001;Jusys et al, 2002].…”
Section: Effect Of Catalyst Structure and Compositionmentioning
confidence: 99%
“…Recently, RTILs have been proposed to be very interesting and efficient pasting binders in place of non-conductive organic binders for the preparation of carbon composite electrodes, 13,14 Although using formaldehyde (CH 2 O) is a risk to human health. But recent data show that formaldehyde fuel cells are attractive alternatives for proton exchange membrane fuel cells 15,16 and researches show that there has been significant interest in the electrochemical oxidation of formaldehyde for many years, [17][18][19] Pt and Pt alloys, 20,21 copper and copper alloys, 22,23 polycrystalline palladium, 24 gold, 25 and palladium nanoparticles on functional multiwalled carbon nanotubes 26 have been studied as anode catalysts for the HCHO oxidation. However, one of the limiting factors is that precious metals (Pt, Pd, Au, etc.)…”
Section: Introductionmentioning
confidence: 99%